2014
DOI: 10.1163/22134808-00002463
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extended Sensory Range via the EyeCane Sensory Substitution Device on the Characteristics of Visionless Virtual Navigation

Abstract: Mobility training programs for helping the blind navigate through unknown places with a WhiteCane significantly improve their mobility. However, what is the effect of new assistive technologies, offering more information to the blind user, on the underlying premises of these programs such as navigation patterns?We developed the virtual-EyeCane, a minimalistic sensory substitution device translating singlepoint-distance into auditory cues identical to the EyeCane's in the real world. We compared perfor mance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The range is set by the user or the device itself and information is converted to an auditory signal that can effectively convey distance from the object to the user (Hughes, 2001 ; Sohl-Dickstein et al, 2014 ) and inform locomotion (Kolarik et al 2014a , b ). Other devices that translate visual patterns into sound have been demonstrated to provide the user with effective distance information and guide motor performance, including the “prosthesis substituting vision with audition” (PSVA, Renier et al, 2005 ), the vOICe (the middle three letters stand for “oh I see"; Meijer, 1992 ), and the EyeCane (Maidenbaum et al, 2013 ; Maidenbaum et al, 2014 ). SSDs have high potential to increase the spatial awareness of the blind and have been utilized in the laboratory to identify multimodal brain areas for depth processing (Renier et al, 2005 ) and to investigate neural plasticity arising as a consequence of visual loss (De Volder et al, 1999 ).…”
Section: Effect Of Visual Loss On Auditory Distance Perceptionmentioning
confidence: 99%
“…The range is set by the user or the device itself and information is converted to an auditory signal that can effectively convey distance from the object to the user (Hughes, 2001 ; Sohl-Dickstein et al, 2014 ) and inform locomotion (Kolarik et al 2014a , b ). Other devices that translate visual patterns into sound have been demonstrated to provide the user with effective distance information and guide motor performance, including the “prosthesis substituting vision with audition” (PSVA, Renier et al, 2005 ), the vOICe (the middle three letters stand for “oh I see"; Meijer, 1992 ), and the EyeCane (Maidenbaum et al, 2013 ; Maidenbaum et al, 2014 ). SSDs have high potential to increase the spatial awareness of the blind and have been utilized in the laboratory to identify multimodal brain areas for depth processing (Renier et al, 2005 ) and to investigate neural plasticity arising as a consequence of visual loss (De Volder et al, 1999 ).…”
Section: Effect Of Visual Loss On Auditory Distance Perceptionmentioning
confidence: 99%
“…Chebat et al [ 10 ] showed that blind participants and blindfolded-sighted controls could use the Eyecane to navigate through real and virtual mazes. In virtual environments, the increased sensory range of 5 m provided by a virtual Eyecane allowed participants to take shorter navigation paths and make fewer collisions than when a virtual white cane was used [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, virtual mazes can, in and of themselves, be used as a rehabilitation tool, for at-home training to navigate through an unfamiliar environment, for individuals with visual impairment (e.g., [ 11 ]). In this scenario, visual information is conveyed via sounds, in what is termed "sensory substitution" (e.g., [ 13 14 , 18 19 ]). It has been demonstrated that learning of new environments in the virtual realm transfers to the corresponding real-world setting [ 11 , 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%